2019
DOI: 10.1002/advs.201901954
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine‐Enabled Photonic Thermogaseous Cancer Therapy

Abstract: Local photothermal hyperthermia for tumor ablation and specific stimuliresponsive gas therapy feature the merits of remote operation, noninvasive intervention, and in situ tumor‐specific activation in cancer‐therapeutic biomedicine. Inspired by synergistic/sequential therapeutic modality, herein a novel therapeutic modality is reported based on the construction of two‐dimensional (2D) core/shell‐structured Nb2C–MSNs–SNO composite nanosheets for photonic thermogaseous therapy. A phototriggered thermogas‐generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 70 publications
1
44
0
2
Order By: Relevance
“…The results showed that the constructed Nb 2 C‐MSNs‐SNO composite nanosheet can be used as an excellent PA contrast agent. [ 125 ]…”
Section: Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the constructed Nb 2 C‐MSNs‐SNO composite nanosheet can be used as an excellent PA contrast agent. [ 125 ]…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [ 125 ] Copyright 2020, Wiley. B, Before and after intravenously injection with Ti 3 C 2 –IONPs–SPs, transverse, coronal section and corresponding signal intensities of the T2‐weighted MRI of 4T1 tumor‐bearing mice were showed.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…MXenes 要实现理想的肿瘤治疗效果需进行表 面功能化修饰,但是 MXenes 表面缺乏足够多的化 学基团结合生物分子或功能性纳米粒子 [33] 。为解决 这一问题, 可在 MXenes 表面构建介孔二氧化硅层。 介孔二氧化硅层具有低的特点,在其表面容易作表 面功能化修饰,便于结合生物分子和功能性纳米粒 子 [58][59][60][61] 。而且,MXenes 表面构建的介孔二氧化硅层 具有较高的比表面积和较大的孔体积,可提高载药 能力并实现化疗药物的可控释放 [33] 。 Yang 课 题 组 [58] 通 过 十 六 烷 三 甲 基 氯 化 铵 (CTAC)在 Ti3C2 表面构建介孔二氧化硅层,成功 制备出 Ti3C2@mMSNs 复合材料(图 5(a)) ,介孔二 氧化硅层的孔结构增强了复合材料在生理溶液中的 亲水性和分散性, 还可以使复合材料按需释放 DOX 药物。 另外,CTAC 也是一种有效杀死肿瘤细胞的药 物分子,Chen 课题组 [59] 在构建 Nb2C 介孔二氧化硅 纳米复合材料时,创新性地将 CTAC 保留于纳米复 合材料中(图 5(b)) ,从而避免了去除纳米复合材料 中残留的 CTAC 的繁琐步骤 [58] Chen 课题组 [60] 又在 Nb2C 纳米材料的介孔二氧化硅 层中孔内负载 AIPH。所构建的 A@Nb2C@Si 复合 纳米材料经 PTT 可促使 AIPH 快速释放并分解产生 自由基,同时实现了自由基的可控生成和释放(图…”
Section: Mxenes 表面介孔负载化疗药物的体系unclassified
“…Thec umulative NO release was observed to be further enhanced by pulsed laser irradiation for all these examined pH states.Upon pulsed laser irradiation, strong thermoelastic expansion with high local temperature around the nanocapsules could probably accelerate the decomposition NO donors to release free NO. [27] Additionally,t he generated strong PA cavitation could potentially enhance the nanocapsule permeability, [28] promoting out-diffusion of NO donors and the released NO.T he pulsed laser-accelerated NO release would potentially decrease the side effects of limited NO release. [29] In addition, typical electrochemical analysis was performed to evaluate real-time free NO release from the dispersion of NO-NCPs via ac ommercial NO electrode ( Figure S5).…”
Section: Angewandte Chemiementioning
confidence: 99%